PROFIL KLT BEBERAPA JENIS KOPI DI SUMATERA DAN POTENSI ANTIOKSIDANNYA - Irwan Sudarmanto (JFL : Jurnal Farmasi Lampung, 2019)
This study shows that the three coffee samples, namely Lampung coffee, Medan coffee and Aceh coffee have the main phytochemical content that is identical with alkaloid compounds, tannins, phenol compounds, tannins and flavonoids. The TLC test is used to be able to confirm the origin of the type of coffee against the polar fraction (ethanol) and nonpolar fraction (chloroform). In this study, the results of the chromatogram were identical so that in this study the use of the TLC method could not be used to determine the biomarkers contained in the coffee samples. The antioxidant potential for Lampung Coffee, Medan Coffee and Aceh Coffee is 15.60 ppm, 13.24 ppm and 13.40 ppm. Keywords: antioxidant, coffee, TLC, phytochemical